Persepsi Akuntan Pajak terhadap Transisi Digitalisasi Perpajakan: Studi Fenomenologi pada Implementasi Coretax - David David; Heru Tjaraka (Politeknik Ganesha Medan, 2026)
The implementation of the Coretax Administration System represents a major stage in the digital transformation of tax administration in Indonesia, aimed at enhancing efficiency, transparency, and tax compliance. However, the initial phase of Coretax implementation has been accompanied by technical disruptions that directly affect professional users of the system. This study aims to explore how tax accountants perceive and make sense of the transition toward digital tax administration through the implementation of Coretax. Using a qualitative phenomenological approach, the study examines the lived experiences of tax accountants who are directly involved in operating the system. Data were collected through semi-structured, in-depth interviews with three tax accountants and analyzed using the NHCEI phenomenological framework (noema, noesis, epoche, and eidetic reduction), combined with thematic analysis. The Slippery Slope Framework was employed as an interpretive conceptual lens to understand perceptions of power and trust toward the tax authority. The findings indicate that Coretax implementation generates an initial adaptation phase requiring substantial technical and procedural adjustment, reshapes work practices toward greater planning and caution, and strengthens perceptions of system-based oversight. Power is experienced through data traceability and limited correction flexibility, while trust develops gradually through procedural clarity and reporting certainty, yet remains contingent on the quality of technical performance. The study concludes that digital tax administration through Coretax reconfigures the relationship between tax accountants and the tax authority, which is experienced through a dynamic interaction between power and trust embedded in everyday professional practice.